2013
DOI: 10.1016/j.plrev.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lightning-triggered electroporation and electrofusion as possible contributors to natural horizontal gene transfer

Abstract: Phylogenetic studies show that horizontal gene transfer (HGT) is a significant contributor to genetic variability of prokaryotes, and was perhaps even more abundant during the early evolution. Hitherto, research of natural HGT has mainly focused on three mechanisms of DNA transfer: conjugation, natural competence, and viral transduction. This paper discusses the feasibility of a fourth such mechanism--cell electroporation and/or electrofusion triggered by atmospheric electrostatic discharges (lightnings). A de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 153 publications
(140 reference statements)
0
31
0
Order By: Relevance
“…The SOS response can also trigger HGT of ARGs, thereby providing a mechanism for the spread of ARGs from exposure to antibiotics (Beaber et al, 2004). Many additional drivers (e.g., chemical and environmental) of HGT have been identified (Hastings et al, 2004; Antonova and Hammer, 2011), including abiotic sources (Warnes et al, 2012; Kotnik, 2013). The relative importance of each of these drivers of HGT has yet to be assessed at an ecologically relevant scale.…”
Section: Drivers Of Resistance: Antibiotic Resistance Genesmentioning
confidence: 99%
“…The SOS response can also trigger HGT of ARGs, thereby providing a mechanism for the spread of ARGs from exposure to antibiotics (Beaber et al, 2004). Many additional drivers (e.g., chemical and environmental) of HGT have been identified (Hastings et al, 2004; Antonova and Hammer, 2011), including abiotic sources (Warnes et al, 2012; Kotnik, 2013). The relative importance of each of these drivers of HGT has yet to be assessed at an ecologically relevant scale.…”
Section: Drivers Of Resistance: Antibiotic Resistance Genesmentioning
confidence: 99%
“…pp. 362-363 in (Kotnik 2013a)). Similarly, an electric field of 30 kV/cm (sufficient for irreversible electroporation of most microorganisms) is induced at a radial distance of ~2 cm, so that within the abovementioned ~100 cm 3 where electroporation can occur, in the inner ~20 cm 3 it is predominantly irreversible (i.e., with high probability of cell death), and in the remaining ~80 cm 3 largely reversible.…”
Section: Do Abiotic Hgt Mechanisms Act In Nature?mentioning
confidence: 99%
“…We have recently suggested that lightning-triggered electroporation of organisms’ envelopes acts as a natural abiotic mechanism of HGT, causing both DNA release and uptake (Kotnik 2013a; Weaver 2013; Kotnik 2013b). In this paper, we approach the topic of abiotic HGT mechanisms more broadly, positing that three physical methods used for artificial genetic transformation – freeze-and-thaw, microbeads-agitation, and electroporation-based transformation – all have prominent analogues in nature: freeze-and-thaw cycles in polar waters, sand-agitation in waters at riverbeds and foreshores, and lightning-triggered electroporation in all aqueous habitats accessible to lightning strokes.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its quick-ness, low cost, and simplicity even when it has a low efficiency, requires laborious protocols for regeneration after genetic transformation, and can only be applied to protoplasts [1,2,[12][13][14][15]. Electroporation is based on the application of a strong electrical field to enhance the formation of pores on the cell membrane due to a polarity alteration, caused by the electrical field (alternated or pulsed) that induces a dipolar moment inside the cells, and a potential difference through the plasmatic membrane [15][16][17][18].…”
Section: Electroporationmentioning
confidence: 99%
“…Electroporation is extremely used to transform yeast, especially Saccharomyces cerevisiae, but the frequency of transformation (up to 1x105 trans-formants per microgram of DNA) is low in comparison with that obtained for bacteria. Due to this, the cell wall of Saccharomyces cerevisiae has been manipulated by using chemical treatments or employing enzymatic cocktails to produce protoplasts before electroporation [30,31].When using protoplasts of plants, fungi or animals, the uptake of DNA can be achieved by electrofusion, i.e., two membranes located very close to each other can be fused by application of an electric field and the DNA present in the cell suspension is trapped in the cytoplasm of the joined cells [13,32]. market in 2001 [33,34].…”
Section: Electroporationmentioning
confidence: 99%